Physicochemical characterization of flours from plant species for the Ecuadorian agroindustry - Escobar, José Antonio (2016)
Flour from mesocarp of the peach palm fruit (Bactris gasipaes Kunth) and the underground corm of taro (Colocasia esculenta (L.) Schott) were obtained through standard agroindustrial procedures. The voucher species are both deposited in the Amazonian Herbarium (ECUAMZ) of the Universidad Estatal Amazónica (UEA). The losses by the selection, cutting, washing, cooking, peeled and dehydration indicated that it is usable as final product peach palm flour (HCHT) by 30% and for taro flour (HPCH) a 25%. Flours were stored vacuum packed for eight months in polyethylene bags, according to microbiological analysis. Regarding moisture, best results were obtained in the HCHT, with less than the maximum specified humidity values for wheat. The parameter HCHT ash was much better than in the HPCH. Both flours showed levels higher than conventional protein flour and therefore it represents an important alternative for the development of agro-industrial products